The Effect of Transitioning to Online Learning on the Academic Performance of Upper Basic Stage Female Students in English Language in Amman District Directorate from their Point of View - Daghmash, Heba Hasan; El-Hanbali, Saba Azzam (Journal of Educational and Psychological Sciences, 2022)
The study aimed at identifying the effect of transitioning to online learning on the academic performance of upper basic stage female students in Amman district directorate. The population was (3953) of upper basic stage female students in Amman District directorate. The sample consisted of (375) female students. The questionnaire consisted of (4) dimensions and (32) statements. It was found that the status quo of the academic performance of upper basic stage female students in English language in Amman district directorate before transitioning to online learning was high. The status quo of the academic performance of upper basic stage female students in English language in Amman district directorate after transitioning to online learning was moderate .There were significant differences in the means to identify the status quo of the effect of transitioning to online learning on the academic performance of upper basic stage female students in Amman district directorate, which came in favour of before transitioning to online learning, there were significant differences in the status quo of the academic performance of upper basic stage female students in English language in Amman district directorate after transitioning to online learning, attributed to Grade and English Language Average Score. Several recommendations were presented.
Keywords: Online Learning; Academic Performance; Upper Basic Stage; Amman District Directorate